Youth engagement: A mixed method investigation of adult and youth perceptions of community resources in rural America. Issue 2 (14th March 2020) - Majee, Wilson; Anakwe, Adaobi
ABSTRACT: This mixed methods study examined how societal perceptions of community resources influence youth leadership development and health promotion. Sixteen community leaders were interviewed, and 31 young adults were surveyed. Friedman's Two-Way ANOVA was used to evaluate variations in perceptions among youth. Qualitative findings highlighted schools and churches as critical in youth leadership development, community involvement, and health promotion. Quantitatively, university extension and schools were most important for leadership development among all youth ( p = .001). Findings underscore the importance of gathering information from youth and adults and call for intergenerational perceptional congruence on community resources.